MOTHER TONGUE ISSUES AND CHALLENGE IN LEARNING ENGLISH AS FOREIGN LANGUAGE - Septianasari, Lina (International Journal of Indonesian Education and Teaching (IJIET), 2019)
Learning English as a foreign language (EFL) is quite challenging to particular learners. Their mother tongue somehow can be such an obstacle in comprehending the language they learn. The interference of their mother tongue more or less influence EFL Learners’ language acquisition. The aims of this research are to find out (1) the interference of learners mother tongue in acquiring English; and (2) the challenge faced by EFL Learners in acquiring English as their foreign language. The population of this sample is EFL learners at University level in Bandung. The researcher used purposive sampling to collect the data. Triangulation is used during the data collection process. Those are observation, test items, and interview. Relevant theories are used to analyze the data. The data shows that the grammatical rule and phonological aspect of learners’ first language affect their language production.DOI: doi.org/10.24071/ijiet.2019.030208